2013
DOI: 10.1037/a0034151
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic influences on negative emotionality and a general psychopathology factor in childhood and adolescence.

Abstract: Previous research using confirmatory factor analysis to model psychopathology comorbidity supported the hypothesis of a broad general factor (i.e., a “bifactor”; Holzinger & Swineford, 1937) of psychopathology in children, adolescents, and adults, with more specific higher-order internalizing and externalizing factors reflecting additional shared variance in symptoms (Lahey et al., 2012; Lahey, Van Hulle, Singh, Waldman, & Rathouz, 2011). The psychological nature of this general factor has not been explored, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
386
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(437 citation statements)
references
References 66 publications
49
386
1
1
Order By: Relevance
“…For example, longitudinal data will be valuable for investigating whether defi cits in cognitive control have a causal role in the co-occurrence of AUD and internalizing disorders. Further, future research could investigate whether defi cits in cognitive control increase risk for general psychopathology, as has been shown for negative emotionality (Tackett et al, 2013). Of note, if found to underlie many mental health disorders, cognitive control could be a focus of behavioral interventions, such as cognitive training (e.g., working memory training; Bickel et al, 2011;Houben et al, 2011) and mindfulness-based therapies (e.g., Baer, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, longitudinal data will be valuable for investigating whether defi cits in cognitive control have a causal role in the co-occurrence of AUD and internalizing disorders. Further, future research could investigate whether defi cits in cognitive control increase risk for general psychopathology, as has been shown for negative emotionality (Tackett et al, 2013). Of note, if found to underlie many mental health disorders, cognitive control could be a focus of behavioral interventions, such as cognitive training (e.g., working memory training; Bickel et al, 2011;Houben et al, 2011) and mindfulness-based therapies (e.g., Baer, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Negative emotionality has been robustly associated with externalizing, internalizing, and general psychopathology (Tackett et al, 2013), and it accounts for a signifi cant proportion of the correlation between externalizing and internalizing disorders (Khan et al, 2005). To extend this work to an investigation of cognitive control, it would be informative to elucidate how negative emotionality and cognitive control, individually and together, relate to the co-occurrence of AUD and internalizing disorders.…”
mentioning
confidence: 99%
“…High negative emotionality may reflect a general risk for psychopathology that may not be strongly specific to AUP, whereas sensation seeking may be more specific to externalizing dimensions of psychopathology (Lahey & Waldman, 2003;Rhee et al, 2015). A study of 6-to 17-yearold twin pairs found that genetic influences on a general factor of internalizing and externalizing psychopathology were correlated with those influencing negative emotionality, whereas genetic influences on the general factor and the specific externalizing factor (but not the internalizing factor) were correlated with sensation seeking (Tackett et al, 2013), indicating the possibility that there may be a more specific genetic overlap for sensation seeking and externalizing disorders. This is also consistent with prior evidence of a Type II subtype of alcohol use disorder in adults, which is characterized as being primarily driven by genetic factors, originating with an earlier onset, and frequently associated with high sensation seeking (Cloninger et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of children and adolescents also have documented the internalizing and disinhibited externalizing spectra, with some evidence suggesting a separate thought disorder dimension (Achenbach, 1966;Achenbach & Rescorla, 2001Achenbach et al, 1991;Laceulle et al, 2015;Lahey et al, 2004Lahey et al, , 2008Lahey et al, , 2011Lahey et al, , 2015Olino et al, 2014;Tackett et al, 2013). Also, some evidence suggests that certain psychopathology dimensions are already present during preschool and do not change appreciably in subsequent years (Sterba et al, 2007(Sterba et al, , 2011.…”
Section: Research and Clinical Applications Of A Quantitative Classifmentioning
confidence: 99%